Failure rate of pterygomandibular block in lower third molar extraction procedures - Sánchez, María del Pilar Rodríguez; Conforte, Jadison Junio; Bonardi, João Paulo; Galafassi, Débora Bressan; Ponzoni, Daniela (ARCHIVES OF HEALTH INVESTIGATION, 2018)
The aim of this study was to evaluate the anaesthetic failure rate of the pterygomandibular technique with an inferior alveolar nerve block in lower third molar extraction procedures. Materials and Methods: A total of 67 healthy patients (men and women, aged between 18–35 years) requiring third molar extractions were selected from the Discipline of Surgery, of the Araçatuba Dental School. The anaesthetic technique utilised was a pterygomandibular block using 2% mepivacaine hydrochloride with epinephrine 1:100,000 (Mepivalem®) in a maximum standardised amount of three tubes (5.4 ml) per procedure (performed by the same operator). Surgical procedures were initiated after confirming the sensation of anaesthesia in the area anesthetised at the inferior alveolar nerve. Painful symptoms were recorded during surgery. Results: In total, 117 surgical procedures, i.e., 114 exodontias and three coronectomies, were performed. During surgical procedures, four patients reported pain during manoeuvres of odontosection, representing an anaesthetic failure rate of 3.41%. Alternative techniques utilised in these four patients involved milohioideo nerve, intraligamentaria, and intrapulpal anaesthesia. Conclusion: The success of inferior alveolar nerve block anaesthesia is difficult to predict due to large anatomical variations, and it is difficult to observe via diagnostic means. The relatively low percentage of anaesthetic failure reported in this study may be related to the number of procedures performed. Descriptors: Anesthesia, Dental; Anesthesia, Local; Molar, Third.